Analysis of Student Mentality with Rating Scale Mental Effort on Online Lecturing - Mira Rahayu; Dino Caesaron; Celline Isabel Elvira Angkuw; Helena Dinda Putri Naila; Muhammad Khalid Asy-syafi’i; Muhammad Rifqi Fahmi Hidayat (International Journal of Innovation in Enterprise System, 2022)
Online lectures are distance learning carried out by all students and teachers who are in separatelocations and involve multiple platforms in the implementation of online lectures. The problemsexperienced by students related to online lectures such as difficulties in using technology, andunderstanding the material so that it triggers a high mental workload from each student. This studyaims to analyze the mental workload of industrial engineering students at Telkom University,Bandung. This study uses the Rating Scale Mental Effort (RSME) method to determine the mentalworkload related to the use of technology in online lectures. In the results of measuring mentalworkload, using a questionnaire distributed to students with 48 respondents. Based on the resultsobtained, the indicator that received the highest average RSME value reached 83.75, on the workanxiety indicator. Therefore, it is necessary to improve online learning and further research.